Rhus coriaria induces autophagic and apoptotic cell death in pancreatic cancer cells - El Mahi, Yassine; Nizami, Zohra Nausheen; Wali, Adil Farooq; Al Neyadi, Aysha; Magramane, Mohamed; Al Azzani, Mazoun; Arafat, Kholoud; Attoub, Samir; Eid, Ali H.; Iratni, Rabah (Frontiers in Pharmacology, 2024)
Pancreatic cancer is a leading cause of cancer-related mortality worldwide with increasing global incidence. We previously reported the anticancer effect of Rhus coriaria ethanolic extract (RCE) in triple negative breast and colon cancer cells. Herein, we investigated the anticancer effect of RCE on human pancreatic cancer cells. We found that RCE significantly inhibited the viability and colony growth of pancreatic cancer cells (Panc-1, Mia-PaCa-2, S2-013, AsPC-1). The antiproliferative effects of RCE in pancreatic cancer cells (Panc-1 and Mia-PaCa-2) were mediated through induction of G1 cell cycle arrest, Beclin-1-independent autophagy, and apoptosis. RCE activated both the extrinsic and intrinsic pathways of apoptosis and regulated the Bax/Bcl-2 apoptotic switch. Mechanistically, we found that RCE inhibited the AKT/mTOR pathway, downstream of which, inactivation of the cell cycle regulator p70S6K and downregulation of the antiapoptotic protein survivin was observed. Additionally, we found that RCE-induced autophagy preceded apoptosis. Further, we confirmed the anticancer effect of RCE in a chick embryo xenograft model and found that RCE inhibited the growth of pancreatic cancer xenografts without affecting embryo survival. Collectively, our findings demonstrate that Rhus coriaria exerts potent anti-pancreatic cancer activity though cell cycle impairment, autophagy, and apoptosis, and is hence a promising source of anticancer phytochemicals.